2011
DOI: 10.1016/j.bbamem.2010.09.004
|View full text |Cite
|
Sign up to set email alerts
|

Impact of the biofilm mode of growth on the inner membrane phospholipid composition and lipid domains in Pseudomonas aeruginosa

Abstract: Many studies using genetic and proteomic approaches have revealed phenotypic differences between planktonic and sessile bacteria but the mechanisms of biofilm formation and the switch between the two growth modes are not well understood yet. In this study, we focused on inner membrane lipidome modifications when Pseudomonas aeruginosa cells were grown as biofilm. Lipid analyses were performed by Electrospray Ionization Mass Spectrometry. Results showed a drastic decrease of the uneven-numbered chain phospholip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
53
0
3

Year Published

2011
2011
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 61 publications
(58 citation statements)
references
References 53 publications
2
53
0
3
Order By: Relevance
“…Membrane composition of Gram-negative bacteria is more complex, containing CFA and cis- and trans -UFA and membrane fluidity also depends on ratios of cis- to trans -UFA and of UFA to CFA. In the literature, results about P. aeruginosa are contradictory as some authors demonstrated a decrease of membrane fluidity in biofilm cells due to increased long chain FA and decreased BCFA (Benamara et al, 2011), whereas others showed a less rigid membrane by decrease in linear SFA content and decrease in fatty acid length chains (Chao et al, 2010). …”
Section: Discussionmentioning
confidence: 99%
“…Membrane composition of Gram-negative bacteria is more complex, containing CFA and cis- and trans -UFA and membrane fluidity also depends on ratios of cis- to trans -UFA and of UFA to CFA. In the literature, results about P. aeruginosa are contradictory as some authors demonstrated a decrease of membrane fluidity in biofilm cells due to increased long chain FA and decreased BCFA (Benamara et al, 2011), whereas others showed a less rigid membrane by decrease in linear SFA content and decrease in fatty acid length chains (Chao et al, 2010). …”
Section: Discussionmentioning
confidence: 99%
“…The headgroup layer was identified as the additional binding region due to cation-π interactions with the choline groups. In the case of E. coli phosphatidylcholine is not the part of the system, but clearly is for P. aerugenosa 65 . It remains to be elucidated whether the headgroup of phosphatidyletholamine, the main E. coli phospholipid, can arrange for indole binding sites.…”
Section: Discussionmentioning
confidence: 99%
“…Transition from the planktonic state to biofilm lifestyle has previously been shown to result in an alteration of the bacterial cell membrane lipid content (46). Consequently, we investigated the fatty acid (FA) composition of the wild-type and ⌬modA strains grown with and without KNO 3 (Fig.…”
Section: Moda Is Required For Mo Acquisitionmentioning
confidence: 99%